Thermal reaction norms between populations with climatic differences of the invader silverleaf whitefly, Bemisia tabaci (Hemiptera: Aleyrodidae) MEAM 1 clade in Colombia. (25th March 2015) - Díaz, Fernando; Saldaña-Guzmán, Cinthya L.; Manzano, María R.; Toro-Perea, Nelson; Cárdenas-Henao, Heiber
Abstract : Insect species can respond adaptively to stress temperature conditions including both thermal limits and reaction norms. In this study, we considered two populations of the whitefly Bemisia tabaci (Gennadius), in which adaptive differentiation was detected for tolerance to upper thermal limits. These two populations are found in two regions of Colombia with climatic differences: the Caribbean region with high environmental temperatures and the Southwest region with lower temperature regimens. We assessed the thermal responses to a range of 1 h heat shocks (37, 39, 41, 43 and 44 °C) performed below the thermal limits for this species. Thermal responses were measured using three life-history traits involved in fitness: survival, fecundity and viability of the offspring after heat shocks. Survival or fecundity as a response to heat shocks did not differ among populations; however, there were significantly different responses for viability between populations. The Southwestern population showed higher viability responses to low heat shocks than the Caribbean population. This relationship suggests a potential trade-off, which appears to be associated with climatic regions. In addition, these results suggest that adaptation under thermal limits does not necessarily involve similar responses throughout the reaction norm. A potential ongoing evolutionary response is taking place through the thermal reaction norms for viability after the invasion by this pest in Colombia.